PHARMACARE, CONTRACEPTION, AND ABORTION IN ONTARIO YOUTH - Downey, Amanda Kathleen (My University, 2025)
Objective: Financial barriers to contraception have been cited as one of the reasons young Canadian females chose less effective methods of contraception, placing them at increased risk of unintended pregnancy. The objective of this thesis was to investigate whether comprehensive and confidential coverage for contraception in Ontario (OHIP+) for individuals under 25 and the amended program, which limited public funding to those without private insurance (OHIP-), were associated with changes in contraceptive dispensations, IUD insertions, and abortions in Ontario youth. Methods: Three studies were conducted to measure each of the above-mentioned objectives. Contraceptive dispensations were extracted at the pharmacy level from September 2016- February 2020; IUD insertions and abortions were extracted using Ontario, Canada population-based data from January 2012-February 2020. Interrupted time series analyses were used to evaluate whether either policy was associated with changes in dispensations, insertions, or abortions in Ontario youth versus control groups, overall and by area-level socioeconomic status. Results: The introduction of OHIP+ was associated with a greater increase in the level of contraceptive dispensations and IUD insertions among Ontario youth versus control groups, while the introduction of OHIP- was associated with declines. The level increase in contraceptives dispensed was greater from pharmacies with lower socioeconomic status; however, area-level socioeconomic status did not modify the association of either policy and IUD insertions. There were no statistically or clinically significant changes in the abortion rate among Ontario youth throughout the study period. Conclusion: The introduction of comprehensive and confidential coverage for contraceptives was associated with an immediate increase in contraceptive dispensations and IUD insertions, while the re-introduction of cost-sharing and loss of confidentiality was associated with a decrease. Reproductive autonomy and the ability to choose an effective contraceptive method of one’s choice should be free of financial barriers and remains an important public health priority.
THE ASSOCIATION BETWEEN PHARMACARE, PRESCRIPTION CONTRACEPTION AND ABORTION IN ONTARIO YOUTH: A TIME-SERIES ANALYSIS
Keywords: Cost sharing; Contraception, Induced / statistics & numerical data; Abortion, Induced / statistics & numerical data; Contraception, Induced / methods; Abortion, Induced / methods; Ontario; Adolescent; Young adult